Investigating prison suicides: The politics of independent oversight - Aitken, Dominic (Punishment & society, 2022)
This article examines the institutional arrangements in place to investigate prison suicides in England and Wales, focusing on inquiries by the Prisons & Probation Ombudsman and coroners’ inquests. The first half of the article is empirical, and draws on a set of elite interviews with Prisons & Probation Ombudsman investigators, senior coroners and other professionals involved in prison oversight. The latter half of the article is theoretical, and interprets prison suicide investigations as an example of broader trends of counter-democracy and depoliticisation. I provide a general theoretical overview of these concepts, and argue that Prisons & Probation Ombudsman investigations and coroners’ inquests operate according to a technocratic logic of independence, neutrality and rationality. The article concludes that prison suicide investigations are narrowly concerned with the factual details and administrative minutiae of individual cases, at the expense of more open ended, less manageable questions about the politics of punishment.